2012
DOI: 10.1007/s10059-012-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Potential Conserved microRNAs and Their Targets in Peach (Prunus persica)

Abstract: 1MicroRNAs are a class of small, endogenous, non-coding RNA molecules that negatively regulate gene expression at the transcriptional or the post-transcriptional level. Although a large number of miRNAs have been identified in many plant species, especially from model plants and crops, they remain largely unknown in peach. In this study, 110 potential miRNAs belonging to 37 families were identified using computational methods. A total of 43 potential targets were found for 21 families based on near-perfect or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…The length distribution of the small RNAs ranged from 18 to 30 nt was examined and shown in Figure 1. In all four samples, 21-nt, 23-nt and 24-nt small RNAs were the major population, consistent with the size of Dicer-like protein cleavage products, and 24-nt was the most dominant, similar to the results obtained from most tested plants, such as Arabidopsis thaliana , rice, tomato, cucumber, apple and peach [7], [9], [10], [11], [16], [17], [31], [32]. The redundancy level of sRNAs was low for the 23-nt and 24-nt sRNAs, while the 21-nt sRNAs have the highest redundancy level, especially in the E24 library.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The length distribution of the small RNAs ranged from 18 to 30 nt was examined and shown in Figure 1. In all four samples, 21-nt, 23-nt and 24-nt small RNAs were the major population, consistent with the size of Dicer-like protein cleavage products, and 24-nt was the most dominant, similar to the results obtained from most tested plants, such as Arabidopsis thaliana , rice, tomato, cucumber, apple and peach [7], [9], [10], [11], [16], [17], [31], [32]. The redundancy level of sRNAs was low for the 23-nt and 24-nt sRNAs, while the 21-nt sRNAs have the highest redundancy level, especially in the E24 library.…”
Section: Resultssupporting
confidence: 84%
“…Genome sequences of apple, peach and strawberry have been generated; however, research in small RNAs of the Rosaceae plant is still limited. Recently, miRNAs from apple and peach were reported [10], [11], [16], [17]. Unlike apple and peach which are important for their fresh fruits, rose is important for its beautiful and fragrant flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these differentially H3K27 trimethylated genes were considered as putative orthologs of Arabidopsis genes after reciprocal blast analysis. Many of these genes encode transcription factors harbouring MADS-box, MYB or NAC domains among others, and epigenetic regulators such as the microRNA ppe-miR172c (Gao et al 2012) and a putative histone acetyltransferase (ppb020787m).…”
Section: Analysis Of Differential H3k27me3 In D and Nd Samplesmentioning
confidence: 99%
“…Recently, some groups have predicted or identified miRNAs and their target genes in peach. Zhang et al [29] and Gao et al [30] independently identified miRNAs by computational prediction and experimentally by verifying miRNAs via RT-qPCR and two miRNA target genes were validated using RLM-RACE. Several miRNAs responsive to drought [31] or chilling [32] and miRNAs in different tissues [28] were identified by high-throughput sequencing in peach.…”
Section: Introductionmentioning
confidence: 99%